AN ANALYSIS OF ENGLISH PHRASAL VERB TRANSLATION IN TOTTO-CHAN NOVEL: THE LITTLE GIRL AT THE WINDOW - Sari, Dwi Indah Mutiara; Sofwan, Ahmad; Kalisa, Pasca (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2017)
This study is attempted to focus on phrasal verb translation of an English novel Totto-chan: The Little Girl at the Window to its Indonesia version entitled Totto-chan: Gadis Cilik di Jendela. The objectives of the study are: (1) to describe the strategies used in translating phrasal verb in the Totto-chan novel (2) to describe the quality of phrasal verb translation in the Totto-chan novel. In conducting this research, descriptive qualitative approach is used. The presentation of discussion is presented in a descriptive way. The data are analyzed by finding the phrasal verbs in the source language and in the target language. The translation strategies are analyzed based on Mona Baker’s theory. Meanwhile, the researcher uses Nababan’s theory to identify the translation quality of the phrasal verbs. The result of the study shows that (1) there are 35 data translated using idiom of similar meaning and form, 155 phrasal verbs translated using an idiom of similar meaning but dissimilar form, 5 phrasal verbs translated by paraphrase and 5 phrasal verbs are translated by omission; it shows that the most strategy used is using idiom of similar meaning but dissimilar form (2) the accuracy level of this novel’s phrasal verb translation is 80,67 % which indicates that the translation is accurate, the acceptability level is 83,17 % which shows us the translation is acceptable and the readability level which is 92,33 % which proves that the translation of this novel is highly readable.